TEACHING CHILDREN OF PRESCHOOL AGE IN NEURODIDACTIC CONDITIONS - Gulyamov Djakhangir Rakhmatullaevich, Nurboev Quvondiq Mirzanovich, Khujakulov Nurmurod Turakulovich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Following article deals with the problem of teaching preschool children in neurodidactic condition, the implementation of modern and innovative pedagogical teaching technologies into practice, revealiling the relationship between age characteristics and the development of memory, attention and thinking skills as well. In addition, the main requirements for didactic materials are highlighted and the significance of their differentiation is scientifically substantiated taking into consideration age and individual characteristics, as well as the characteristics of the organization of the child’s brain activity. Pedagogical conditions for the effective teaching children in preschool educational institutions are proposed as well.